2014
DOI: 10.2147/ijn.s59753
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles promote osteogenic differentiation of human urine-derived stem cells at noncytotoxic concentrations

Abstract: In tissue engineering, urine-derived stem cells are ideal seed cells and silver nanoparticles (AgNPs) are perfect antimicrobial agents. Due to a distinct lack of information on the effects of AgNPs on urine-derived stem cells, a study was conducted to evaluate the effects of silver ions and AgNPs upon the cytotoxicity and osteogenic differentiation of urine-derived stem cells. Initially, AgNPs or AgNO 3 were exposed to urine-derived stem cells for 24 hours. Cytotoxicity was measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 31 publications
2
79
0
Order By: Relevance
“…AgNPs have a dual role: at lower concentrations, they can enhance cell survival and differentiation, and at higher concentrations, they can inhibit cell viability in neuronal cells [27]. For instance, AgNPs with an average size of 20 nm and at concentrations up to 2 µg/mL promoted osteogenic differentiation of urine-derived stem cells by inducing actin polymerization and activation of RhoA; whereas AgNO 3 had no such effects [28]. To determine the effect of AgNPs on cell survival of four different subpopulations of OvCSCs, we first examined the dose-dependent effect of AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs have a dual role: at lower concentrations, they can enhance cell survival and differentiation, and at higher concentrations, they can inhibit cell viability in neuronal cells [27]. For instance, AgNPs with an average size of 20 nm and at concentrations up to 2 µg/mL promoted osteogenic differentiation of urine-derived stem cells by inducing actin polymerization and activation of RhoA; whereas AgNO 3 had no such effects [28]. To determine the effect of AgNPs on cell survival of four different subpopulations of OvCSCs, we first examined the dose-dependent effect of AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…hMSCs exposed to different concentrations of AgNPs exhibited no significant changes in alkaline phosphatase activity, osteocalcin gene expression, osteopontin expression, and mineralization [101]. Similarly, AgNPs had no effect on osteogenic differentiation when human urine-derived stem cells were incubated with non-cytotoxic concentrations [102]. …”
Section: Cellular Effects Of Agnps In Stem Cellsmentioning
confidence: 99%
“…20 Recent advancements in stem cell research show that stem cells used as seed cells have unique properties that are vital to the development of engineered tissue constructs, including high proliferation rates, self-renewal, and specialized differentiation under specific conditions. 21 In addition, differentiated stem cells are less resistant to chemotherapy than non-differentiated cells. AgNPs act as either differentiation-inducing or cytotoxic agent, depending on their concentration and the cell type.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, AgNPs were shown to promote osteogenic differentiation of urine-derived stem cells by inducing actin polymerization, increasing cytoskeletal tension, and activating RhoA. 21 In contrast, AgNPs were found to inhibit differentiation via autophagy blockade and lysosomal impairment in THP-1 monocytes. 22 Several studies have reported that AgNPs play an important role in tissue engineering scaffolds, with a reduced incidence of infection and significant cell compatibility.…”
Section: Introductionmentioning
confidence: 99%